The Mutational Landscape of SARS-CoV-2 Variants of Concern Recovered From Egyptian Patients in 2021 - Seadawy, Mohamed G.; Binsuwaidan, Reem; Alotaibi, Badriyah; El-Masry, Thanaa A.; El-Harty, Bassem E.; Gad, Ahmed F.; Elkhatib, Walid F.; El-Bouseary, Maisra M. (Frontiers in Microbiology, 2022)
In December 2019, a mysterious viral pneumonia first developed in Wuhan, China, resulting in a huge number of fatal cases. This pneumonia, which was named coronavirus disease 2019 (COVID-19), was attributed to a novel coronavirus, SARS-CoV-2. The emerging SARS-CoV-2 mutations pose the greatest risk to human health because they could result in an increase in the COVID-19 severity or the failure of current vaccines. One of these notable mutations is the SARS-CoV-2 Delta variant (B.1.617) that was first detected in India and has rapidly expanded to 115 countries worldwide. Consequently, in this study, we performed next-generation sequencing and phylogenetic analysis of SARS-CoV-2 during the third wave of the pandemic to determine the SARS-CoV-2 variants of concern (VOC) prevalence in Egypt. We observed several mutational patterns, revealing that SARS-CoV-2 evolution has expanded in Egypt with a considerable increase in the number of VOC. Therefore, the Egyptian authorities should take an appropriate approach to investigate the compatibility of already employed vaccines with this VOC and to examine the efficacy of the existing therapeutic regimen against new SARS-CoV-2 variants.